Algoritma Klasifikasi Data Mining Untuk Memprediksi Siswa Dalam Memperoleh Bantuan Dana Pendidikan - Senna Hendrian (Faktor Exacta, 2018)
Education is one of the components of life that can support the success of a person towards life that much better again. Especially for the children that are in the scope of the age of compulsory education. but not all children can attend compulsory education, because several factors cause, one of which is the issue of tuition fees. To cope with the existing problems, then a standalone compiled Bina Bangsa School programs Help Fund education for students who are considered less capable in economic strata. In this study, the author uses the classification Algorithm Datamining Algorithm C4.5 to predict students in obtaining the help of the EducationFund. Sample data are drawn from the Upper secondary school (HIGH SCHOOL) Selfsustaining Bina Bangsa (BBM) that located in Kecamatan Gunungputri Kab. Bogor. From the results of testing and Validation of tests used Cros Confusion Matrix and ROC Curves. The results obtained for the value of Accuracy Algorithm C 4.5 is 98.80%, a value for the Precision of 98.02%, and the value for Sensitivity or Recall of 99.00%. Thus the algorithm C 4.5 is the best techniques and algorithms to predict Students in obtaining the help of the Education Fund. Keywords : data mining, algorithms of classification, algorithm C 4.5, the education fund